Disfigurement formation and control in drilling carbon fibre reinforced composites. (14th January 2008) - Jin, Z.J.; Bao, Y.J.; Gao, H.
Based on the analysis of various disfigurements of carbon fibre resin reinforced composites formed in drilling process, the drilling burr formation model is built up. Analysis results showed that the delaminating disfigurements in the entrance side of drilling mainly belong to Type III cracking breakage caused by drilling torque and the burr disfigurements in the exit side mainly belong to Type I avulsion breakage caused by axial force. Furthermore, two kinds of methods to evaluate the degree of burr and avulsion for drilled carbon fibre resin reinforced composites workpieces are put forward and reasonable drilling parameters for less or even no disfigurements are shown.